Analisis Kualitas Yogurt Santan Kelapa Dengan Penambahan Tepung Kolang Kaling Selama Penyimpanan - Rizki Amelia Nasution; Efrida Pima Sari Tambunan (Journal of Pharmaceutical and Sciences, 2026)
The addition of flour from kolang kaling in this research aims to act as a stabilizer and improve the quality of fermented drinks (yoghurt) made from coconut milk. This research aims to analyze the quality of coconut milk yogurt with the addition of kolang kaling flour by testing its physicochemical properties. Experimental research with coconut milk yogurt samples with the addition of 1% kolang kaling flour and without the addition was stored at 40C for 14 days and analyzed for pH, viscosity and total LAB, as well as testing the research samples for water content using the distillation method (thermovolumetric), protein using the method Kjeldahl, fat using Soxhlet extraction, carbohydrate (starch) content testing using the UV Visible spectrophotometric method, and total acid using the titration and organoleptic method with 9 hedonic scales. Research shows that the results of adding palm fruit flour have an effect on the analysis parameters and are in accordance with SNI, namely pH reaches 5-3.94, carbohydrates decrease during H14 fermentation by 20.1%, protein reaches 6.5%, fat around 3%, water content is very low, namely 49%, The viscosity is very low, namely 2.8cP, the acid number is sufficient according to SNI in H14, namely 2%, %, as well as the hedonic results during storage which show statistical test results which are significantly different (P<0.05) on day 7 and day 14. The research can be concluded based on physicochemical analysis and conformity with SNI that the quality of coconut milk yogurt with the addition of kolang kaling flour during storage is good and in accordance with food standards.